A comparison of the sealing abilities between Biodentine and MTA as root-end filling materials and their effects on bone healing in dogs after periradicular surgery (Journal of Applied Oral Science, 2022)
Objectives: To compare the sealing ability and biocompatibility of Biodentine with mineral trioxide aggregate (MTA) when used as root-end filling materials. Methodology: The Cell Counting Kit-8 (CCK-8) assay was used to compare the cytotoxicity of MTA and Biodentine. Twenty-one extracted teeth with a single canal were immersed in an acidic silver nitrate solution after root-end filling. Then, the volume and depth of silver nitrate that infiltrated the apical portion of the teeth were analyzed using micro-computed tomography (micro-CT). Seventy-two roots from 3 female beagle dogs were randomly distributed into 3 groups and apical surgery was performed. After six months, the volume of the bone defect surrounding these roots was analyzed using micro-CT. Results:Based on the results of the CCK-8 assay, MTA and Biodentine did not show statistically significant differences in cytotoxicity (P>0.05). The volume and the depth of the infiltrated nitrate solution were greater in the MTA group than in the Biodentine group (P<0.05). The volume of the bone defect was larger in the MTA group than in the Biodentine group. However, the difference was not significant (P>0.05). The volumes of the bone defects in the MTA and Biodentine groups were smaller than the group without any filling materials (P<0.05). Conclusions: MTA and Biodentine exhibited comparable cellular biocompatibility. Biodentine showed a superior sealing ability to MTA in root-end filling. Both Biodentine and MTA promoted periradicular bone healing in beagle dog periradicular surgery models.